The Impact of Gadgets on the Social and Emotional Development of Early Childhood - Fildzah Farahiyah; Nita Rosalita; Okti Hazrati (Penerbit Hellow Pustaka, 2024)
This study was conducted to describe the impact of gadgets on early childhood socio-emotional development. The method used in this research is literature methodology. With a qualitative approach. From the results of this study, it is found that gadgets can have positive and negative impacts on the socio-emotional development of early childhood. The positive impacts include: increasing children's imagination and creativity, increasing children's intelligence and cognitive abilities, helping children learn and understand the surrounding environment, increasing children's self-confidence, expanding children's friendship networks. While the negative impacts include: increasing the risk of gadget addiction, reducing children's social interaction with peers, disrupting children's emotional and moral development, increasing the risk of health problems, such as obesity, sleep disorders, and visual impairment.